A lightweight architecture for IoT based on blockchain, designed for constrained IoT devices - Yassin Elgountery; Mohamed Aghroud; Meryem Lasaad; Mohamed Oualla (Institute of Advanced Engineering and Science, 2026)
Blockchain is a technology that is evolving day by day, characterized by features such as security, decentralization, immutability, traceability, and privacy protection. These features make it a promising solution for internet of things (IoT) systems. However, the inherent constraints of IoT devices in terms of storage, computation, energy capacity, and other aspects present significant challenges to integrating blockchain into these systems. This emphasizes the necessity of developing a lightweight solution that considers these specific constraints. This conceptual article proposes a lightweight architecture based on delegated nodes, centered on blockchain technology, and an optimized practical byzantine fault tolerance (PBFT) consensus algorithm, to ensure scalability and reliability for IoT. Moreover, to reduce the storage overhead in the blockchain, an off-chain cloud-based storage solution is proposed in this article. The proposed architecture is designed to prevent direct IoT device-blockchain interactions. All system operations are defined in a single smart contract, which helps reduce the complexity and overhead of the system.